Think Tanks y Centros de Estudio. Los nuevos mecanismos de influencia política en el Chile post-autoritario - Manuel Gárate (Nuevo mundo - Mundos Nuevos, 2008)
The circulation of ideas uses several instruments in the realm of policymaking and economics. Historically, universities, illustrated elites and political parties have accomplished this role. However, since the end of the 1970s it is possible to detect the proliferation of a special type of organization called Think Tanks, which under the form of foundations, study centers or private corporations, work as laboratory where ideas and mechanisms of influence are created to serve different interest groups. Following the American pattern of a "market of ideas" where it seems that what matters in decision making is not democratic legitimacy but the influence over the bureaucrats who provide planning and management in policymaking, these organizations have proliferated to a global level, especially after the fall of the Berlin Wall. Chile is considered within this trend, although it adopted an early and peculiar evolution as a consequence of its recent history. Our research deals precisely with the way these local organizations arise and how they may alter the style of policy making in the country.